Key Problems of Elaborating Multi-Targeted Strategies to Adapt Small and Medium Business Organizations to External Environment Uncertainty - M. S. Kamionsky (Вестник Российского экономического университета имени Г. В. Плеханова)
The article explains the reason for aggravation of some problems of strategic nature in organizations of small and medium business. Difficulties in choosing and applying technologies and methods of working-out and realizing strategies were studied. Principle technology of elaborating strategy of adaptation to conditions of external uncertainty was presented, whose use aims at taking into account factors common for all organizations and unique conditions of each organization work. The system of building a collective entity of strategic management in the form of the so-called distributed participation of employees in development and realization of strategy. Specificity of the new role of company executive in strategic management was described. The author showed a change in the idea of strategy from status of document to status of consciousness element of all company employees.